Multilocus molecular phylogeny of Gasteropelecidae (Ostariophysi: Characiformes) reveals the existence of an unsuspected diversity - Abe, Kelly T. [UNESP]; Mariguela, Tatiane C. [UNESP]; Avelino, Gleisy S. [UNESP]; Castro, Ricardo M.C.; Oliveira, Claudio [UNESP] (Elsevier, 2013)
The characiform family Gasteropelecidae, the so-called freshwater hatchetfishes, is comprised of three genera and nine species found in Panama and all South American countries except Chile. Our goal was to investigate the molecular characteristics, phylogenetic relationships among the species and genera of Gasteropelecidae and phylogenetic relationships between the Gasteropelecidae family with other Characiformes. DNA fragments from two mitochondrial (16S rRNA and Cytochrome B) and three nuclear genes (Rag1, Rag2 and Myh6) were sequenced. Our results corroborate the morphology-based hypothesized monophyly of the Gasteropelecidae family and most of the relationships among its genera. However, the genus Gasteropelecus is polyphyletic because G. maculatus is placed as the sister group to all other gasteropelecids, whereas G. sternicla is more closely related to species of Carnegiella. Similarly, the species Carnegiella strigata is not monophyletic, which suggests that the family needs a taxonomic review. Moreover, the species Thoracocharax stellatus was composed by four distinct lineages suggesting the this species may represents a species complex. © 2013 Elsevier Inc.
Keywords: Characiforms; Evolution; Hatchetfishes; Phylogeny; Systematics